Women's wrist and elbow at work: analysis of acute injuries and cumulative trauma disorders to improve ergonomics in female-dominated activities. Issue 11 (2nd November 2022) - Salerno, Silvana; Giliberti, Claudia
Abstract: The aim of this study is to analyse women's wrist and elbow acute work injuries together with cumulative trauma disorders, such as carpal tunnel syndrome (CTS) and epicondylitis. Five years records (2015–2019) on women's wrist/elbow acute work injuries and CTS/epicondilytis, from Italian National Compensation Authority, were collected and pooled all together as 'dis-ac' (disorders + acute) events. A statistical analysis was performed in comparing the different female-dominated work sectors. Results showed that hairdressing/laundry sector was associated with the highest risk for wrist acute work injuries and cleaning for elbow while manufacturing for CTS and epicondylitis. Hairdressing/laundry and manufacturing were associated with the highest risk for dis-ac events (hairdressing: wrist dis-ac OR: 4.89; CI 95% 4.22–5.67; elbow dis-ac OR: 3.70; CI 95% 2.99–4.58; manufacturing: wrist dis-ac OR: 3.39; CI 95% 3.13–3.66; elbow dis-ac OR: 2.45; CI 95% 2.20–2.73). The relationship between acute injuries and cumulative trauma disorders is discussed to preserve women's safety and health in ergonomics. Practitioner Summary: Women's wrist and elbow acute work injuries and cumulative trauma disorders (carpal tunnel syndrome and epicondylitis) were analysed and studied all together (dis-ac events) in female-dominated activities. Hairdressing and manufacturing work sectors were associated with the highest risk, showing the need to safeguard the health and safety of female workers.